2022
DOI: 10.1590/s1677-5538.ibju.2021.99.11
|View full text |Cite
|
Sign up to set email alerts
|

Testicular arteries anatomy applied to fowler-sthephens surgery in high undescended testis – a narrative review

Abstract: Objectives: In this review we will describe the testicular vessels anatomy and the implications of these vessels in surgical treatment of high undescended testis. Material and Methods: We performed a narrative review of the literature about the role of the testicular arteries anatomy in the treatment of high undescended testis. We also studied two human testes to illustrate the testicular vascularization. Results: Each testis is irrigated by three arteries: testicular artery (internal spermatic artery), a bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Irrespective of the surgical technique, preservation of an adequate arterial supply for the testes is crucial for successful orchidopexy to ensure normal testicular size and texture ( 19 ). The anatomy of testicular arteries is very important to the success of the surgical procedures ( 11 , 20 ). Each testis is irrigated by three arteries: the testicular artery (internal spermatic artery), a branch of the aorta; deferential artery (vasal artery), a branch of the inferior vesicle artery that originates from the anterior trunk of internal iliac artery and cremasteric artery (external spermatic artery), a branch of the inferior epigastric artery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Irrespective of the surgical technique, preservation of an adequate arterial supply for the testes is crucial for successful orchidopexy to ensure normal testicular size and texture ( 19 ). The anatomy of testicular arteries is very important to the success of the surgical procedures ( 11 , 20 ). Each testis is irrigated by three arteries: the testicular artery (internal spermatic artery), a branch of the aorta; deferential artery (vasal artery), a branch of the inferior vesicle artery that originates from the anterior trunk of internal iliac artery and cremasteric artery (external spermatic artery), a branch of the inferior epigastric artery.…”
Section: Discussionmentioning
confidence: 99%
“…Each testis is irrigated by three arteries: the testicular artery (internal spermatic artery), a branch of the aorta; deferential artery (vasal artery), a branch of the inferior vesicle artery that originates from the anterior trunk of internal iliac artery and cremasteric artery (external spermatic artery), a branch of the inferior epigastric artery. These three arteries penetrate the organ in the mediastinal region, where they provide ample communication ( 11 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gubernaculum is the most important structure in the inguinoscrotal stage of testicular migration (1, 2). The knowledge of testicular and gubernaculum vascular anatomy is a key point in this procedure (3). In this paper the authors retrospectively studied a cohort of patients who underwent laparoscopic first-stage FSO and open versus laparoscopic gubernaculum-sparing second-stage FSO and concluded that the second-stage gubernaculum-sparing FSO achieved high testicular survival rates and satisfactory testicular positions.…”
Section: Commentmentioning
confidence: 99%